2002
DOI: 10.1034/j.1600-0528.2002.00016.x
|View full text |Cite
|
Sign up to set email alerts
|

Do young adults demand more dental services as their income increases?

Abstract: Several studies from the USA have shown that there is a positive and strong relationship between income and demand for dental care. All these studies have been performed on populations where treatment needs were high. Today, young adults represent one group of the population where treatment needs are low. But young adults will not necessarily demand or utilize more dental services as their income increases. As we do not know the extent to which demand will increase when income increases among young adults, fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
10

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 30 publications
3
23
0
10
Order By: Relevance
“…Adolescents belonging to the less poor households presented with treatment need and dental attendance more frequently than their counterparts in the poorest households. According to Grytten and Holst [27], several US studies reported a positive association between income and demand for dental care, particularly when treatment need was high. Although dental attendance, oral hygiene behavior and sugar intake varied systematically with oral health outcomes (Table 3), social disparities in caries experience and self reported oral health were not attenuated whilst adjusting for those lifestyle patterns (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents belonging to the less poor households presented with treatment need and dental attendance more frequently than their counterparts in the poorest households. According to Grytten and Holst [27], several US studies reported a positive association between income and demand for dental care, particularly when treatment need was high. Although dental attendance, oral hygiene behavior and sugar intake varied systematically with oral health outcomes (Table 3), social disparities in caries experience and self reported oral health were not attenuated whilst adjusting for those lifestyle patterns (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…According to Grytten and Holst,19 several US studies reported a positive and strong relation between income and demand for dental care when treatment need is high, and less pronounced associations when need is low. However, dental attendances have little effect on reducing dental caries 20 21 although access to dental care may improve the quality of life of affected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Regular dental attendance is mostly defined by at least one dental visit, on average, per year during the last 5 yr, or at least one dental visit during the past year. In Scandinavian and other western countries, the number of regular users of oral health services has increased over time, including older people (1, 3–6). Factors consistently associated with people's dental visiting habits are number of teeth present, age, and gender, but socio‐cultural and socio‐economic factors have also been found to affect people's dental attendance (1, 2, 4–8).…”
mentioning
confidence: 99%